1970
DOI: 10.1037/h0029904
|View full text |Cite
|
Sign up to set email alerts
|

Key influences of occupational preference among black youth.

Abstract: Using a longitudinal sample of 583 males, this research examined the relationships among selected ascribed and achieved traits and their relationships to occupational attainment.American culture is marked by a central stress upon personal achievement, especially secular occupational achievement. The "success story" and the respect accorded to the self-made man are distinctly American. Our society has been highly competitive-a society in which ascribed status in the form of fixed, hereditarysocial stratificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
2

Year Published

1976
1976
1989
1989

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 8 publications
0
13
2
Order By: Relevance
“…Pallone et al (1970) found that parental occupational role models of the same gender as the child were the most important influences on the child's choice of a future occupation. An experimental study conducted by Little and Roach (1974) demonstrated that women who observed videotaped models being reinforced for their non-traditional career choices were more likely to express a preference for the same occupations as the models than were women who had not been exposed to the models.…”
Section: Social Learning Theory Career Selection and The Entrepreneurmentioning
confidence: 99%
“…Pallone et al (1970) found that parental occupational role models of the same gender as the child were the most important influences on the child's choice of a future occupation. An experimental study conducted by Little and Roach (1974) demonstrated that women who observed videotaped models being reinforced for their non-traditional career choices were more likely to express a preference for the same occupations as the models than were women who had not been exposed to the models.…”
Section: Social Learning Theory Career Selection and The Entrepreneurmentioning
confidence: 99%
“…Several studies have examined the influence of parents on the occupational choice or preference of adolescents. Only Anglo and Black adolescents were included in some studies (Pallone, Rickard, & Hurley, 1970); Puerto Rican, Black, and Anglo adolescents were used in other studies (Pallone, Hurley, & Rickard, 1973); and adolescents' ethnic or cultural group was unclear in others (Brunkan, 1965;Jacobson, 1971). The parental influence in these studies, except for Jacobson (1971), was based solely on adolescent self-reports.…”
mentioning
confidence: 99%
“…The parental influence in these studies, except for Jacobson (1971), was based solely on adolescent self-reports. For example, Pallone, Rickard, and Hurley (1970) and Pallone, Hurley, and Rickard (1973) found that parents were the principal influence (among other influences) on adolescents' expected occupations. Brunkan's (1965) results indicated a nonsignificant relationship between males' vocational choices and degree of identification with their father or mother; however, there was a significant relationship between vocational interests and degree of identification with their parents.…”
mentioning
confidence: 99%
“…A few studies have dealt with counselor-client contact and vocational choice in general terms [3; 23; 24]; there is even less data relating specifically to the role of the school counselor in occupational decision making. In addition to studies by Deffenbacher and Kemper [8] and Leubling [17], Pallone, Rickard, and Hurley [18] found that, although counselors influence occupational preference, they ranked somewhat behind others in students' social milieu in terms of importance. On the other hand, Hanson and Sander [10], in a study dealing with realism of occupational choice, found that both "overshooters" (who had participated in group counseling sessions) and "undershooters" (who had been involved only in individual counseling) showed increased movement toward realistic choices.…”
Section: Review Of Literature and The Research Problemmentioning
confidence: 85%